Development of Emotional Intelligence of Future Teachers of Professional Training - Чубрей, Олександра; Kovalchuk, V; Prylepa, I; Marynchenko, I; Opanasenko, V; Marynchenko, Y (International Journal of Early Childhood Special Education (INT-JECSE), 2022)
The problem of the development of emotional intelligence of future specialists in vocational education is investigated. It is established that emotional intelligence is the subject of scientific knowledge of modern domestic and foreign research. Based on the analysis of scientific and pedagogical works of scientists and the real practice of emotional intelligence, it is established that the modern labor market needs workers with a set of technical, soft, and social skills that can change according to the requirements associated with work. It has been proven that investing in skills development is critical in a country's economic growth and competitiveness. Among the necessary skills of a modern specialist, we have identified: comprehensive problem solving, critical thinking, mobility, creativity, leadership, time management, coordination with others, emotional intelligence, judgment and decision making, guidance service, negotiation, cognitive flexibility. At the theoretical level, the psychological features of the formation of emotional intelligence of future professionals in the specialization 015.36 - Vocational education are substantiated, the technology of light industry products and 015.37 - Vocational education. Agricultural production, processing of farm products, and food technology have scientifically identified ways to form emotional intelligence (involving future teachers of vocational training in various activities: game, project, cooperative, research; establishing parity in the system of interaction "student - student," "teacher - group of students," "student - group of students "; introduction of active teaching methods ("openwork saw," "pyramid," "brainstorming," etc.). The article substantiates the need and possibilities of forming the emotional intelligence of the future specialist during the student period
Keywords: Emotional Intelligence; Training of future Professionals; Criteria for the Formation of Emotional Intelligence; Professional Education